A sub-imperial realm amidst the global parliamentary moment: legislative imaginations of Russian Poland, 1905–18. (2nd September 2022) - Marzec, Wiktor
ABSTRACT: This article seeks to explore the ideal of parliament nurtured by various political actors in the Russian-controlled Kingdom of Poland, up to the formation of the Polish nation state after the interim German occupation. Spanned between the legacy of the noble Sejms and radical democratic ideas for future Poland, the cultural imagination of parliamentarism faced its imperfect embodiment in the existing imperial assemblies – above all, the Russian Duma . Drawing from an extensive collection of political leaflets, press of various profiles and Russian administrative sources, I demonstrate the entangled, lived relationship between parliament and revolution, by no means opposite concepts in the global wave of constitutional revolutions. The parliamentary ideal served to renegotiate the arrangements of imperial social space in the direction of national self-assertion and perpetuated social practices conductive to future democratic arrangements. The actors involved demonstrated ambiguous potentials of various forms of national representation. These experiences and considerations had grave consequences in the critical juncture of the revolutionary sequence leading to the emergence of the Polish nation state – for the time being, in a majoritarian parliamentary form.